Mobile Health Assisted Self Monitoring in Heart Failure Patients To Ensure Quality of Life: A Scoping Review - Indriany, Finna; Siregar, Kemal N.; Purwowiyoto, Budhi Setianto (Indonesian Journal of Medicine, 2024)
Background: Heart failure leads to reduced quality of life, high hospitalization rates, mortality rates, and treatment costs where out-of-hospital self-monitoring can help with management and prevention of hospitalization and digital apps can help with this. The purpose of this review was getting all information of the studies regarding self-monitoring assisted by mobile health or digital application for heart failure patients.Subjects and Method: Using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Protocols for a Scoping Review (PRISMA-ScR), literature searches were developed by searching the databases: PubMed.gov, ScienceDirect, SpringerLink, Google Scholar. Following the eligibility criteria, articles that included were analyzed to get the result.Results: Mostly the studies were conducted in 2016 and 2017 (20% each, n=5), less studies in 2018, 2019, 2020, and increased again in 2021 (16%, n=4). The studies were done 57% in USA (n=13), both Australia and Canada were 9% (n=2), and other countries. The designs of the studies were mostly RCT (74%, n=17). Sample size was variative mostly less than 50 participants (39%, n=9). There were 65% of the studies measured the daily body weight (n=15), others used vital signs 57%, medication adherence 39%, and other items. QoL was the most in the outcome (61%, n=14). Main findings mostly showed positive impact on self-monitoring with digital application.Conclusion: Using mobile apps for heart failure patients’ self-monitoring created the positive impacts in the expected outcomes, mostly for quality of life.